Special report of the world's women 2005 : progress in statistics : focusing on sex-disaggregated statistics on population, births and deaths (UN New YorkUS, 2005)
Presents an interim report focusing on population, births and deaths, which will form part of the first chapter of the full report entitled 'The world's women 2005 : progress in statistics'.
Keywords: WOMEN